(untitled) (TAJ: Journal of Teachers Association, 2022)
Background: Nationwide vaccination against SARS CoV-2 is the hope for stopping the pandemic and death from COVID-19. Till today several vaccines have been developed. In Bangladesh, the Covishield vaccine was the first coronavirus vaccine that was administered to health care workers on a priority basis. To assess antibody response in our community, evaluation of response in this group was necessary. Objectives: Our main aim of this study was to evaluate antibody response to SARS CoV-2 after vaccination with the Covishield vaccine in health care workers. Patients and Methods: It was a cross-sectional type study. Eighty-seven purposively collected health care workers were included in the study. Demographic profile, Co-morbidities, and other variables were recorded in a questionnaire. Blood samples were collected to assess SARS CoV-2 specific antibody. Results: Mean age in our study was 41.29±7.87 years. Most of them were between 35 to 44 years of age. Male: Female ratio was 3.35:1. Obesity (BMI>25) was present in 25.9% of individuals, hypertension in 33.3%, and DM in 14.9% of individuals. Overall 82.8% were vaccinated with the Covishield vaccine, and the remaining were not vaccinated. 96.6% were found to be antibody positive. All individuals (100%) who were either had a history of COVID-19 or received at least one shot of the Covishield vaccine were found antibody positive. Conclusion: Covishield vaccine was found to be highly effective in producing antibody response among healthcare workers. TAJ 2021; 34: No-2: 01-08